English vs. Dutch high secure hospitals: service user perspectives - Völlm, Birgit (Emerald, 2017)
Purpose: The aim of this paper is to describe service users’ perspectives on the difference between high secure long-stay forensic psychiatric services in the Netherlands and high secure forensic psychiatric care in England. These perspectives are relevant in considering the benefits of a similar long-stay service in England. Method: A current in-patient detained in a high secure hospital in England and other mental health service users and carers with experience in forensic-psychiatric settings were asked to watch a documentary on a Dutch high secure long-stay service. Then they were invited to make comparisons between this service and high-secure care in England. These perspectives were gained in the context of their membership of the Service User Reference Group of an externally funded study on long-stay in forensic-psychiatric settings in England. Findings: Our small group of participants highlighted the importance of relational security, meaningful occupation, autonomy, positive therapeutic relationships with staff and a homely environment for those with lengthy admissions and perceived these to be better met in the Dutch service. These factors might contribute to improved quality of life that services should strive to achieve, especially for those with prolonged admissions. Practical Implications: Perspectives of service users with lived experience of long-stay in forensic settings are important in informing service developments. Lessons can be learnt from initiatives to improve the quality of life of long-stay services in other countries and consideration be given on how to best manage this unique group. Originality/Value: To our knowledge this is the first study asking service users about their view on forensic services in other countries. Our findings suggest that service users have valuable contributions to make to aid service developments and should be involved in similar such exercises in the future.